ملامح تطبيق نظرية الموازنة بين المنافع والمضار في مجال نزع الملكية للمنفعة العامة : دراسة مقارنة ( فرنسا - مصر - المغرب - ليبيا - الاردن ) - مرشحة، عمار وحيد; الغندور، محمد سعيد (جامعة البحرين - كلية الحقوق, 2014)
تعد المنفعة العامة مناط نزع الملكية الخاصة، ونتيجة اتساع مفهوم المنفعة العامة كان لزاماً على القضاء أن يمارس رقابة فعالة على السلطة التقديرية للإدارة في تقدير أوجه المنفعة العامة لكبح جماح أوجه الانحراف التي قد تشوب قراراتها، وكان من نتيجة التطورات القضائية المتلاحقة التي مر بها مجلس الدولة الفرنسي ابتداعه لنظريات جديدة سعى من خلالها إلى تحقيق رقابة فعالة على تقديرات الإدارة في شتى مجالات نشاطها الإداري، ومن بين هذه النظريات نظرية الموازنة بين المنافع والمضار والتي أرساها بقراره الصادر في قضية Est Novelle Vill بتاريخ 28/05/1971 وفي ضوء هذه النظرية بدأ مجلس الدولة الفرنسي بإجراء عملية موازنة بين المنافع والمضار، أو المزايا والخسائر، التي قد تترتب على القرارات التي تصدرها الإدارة بنزع الملكية للمنفعة العامة، وتقدير مشروعية هذه القرارات نتيجة لذلك. لذا سنتناول في بحثنا المتواضع هذا مفهوم نظرية الموازنة بين المنافع والمضار في مجال نزع الملكية للمنفعة العامة، وموقف الفقه المؤيد والمعارض لها وحجج كل منهما، ومن ثم سنبين أهم تطبيقات القضاء الإداري الفرنسي لنظرية الموازنة في مجال نزع الملكية، ومن ثم سنتكلم عن موقف كل من القضاء الإداري المصري والمغربي والليبي والأردني من هذه النظرية، ومن ثم نختم بأهم النتائج والتوصيات التي توصلنا إليها في بحثنا المتواضع هذا. The public intrest is entrusted with private property dispossession and as a result of the expansion of the concept of the public benefit, judiciary is imposed on to practice effective control upon the estimation authority for the administration in estimating the aspects of the public benefit to stop the deviation aspects that may spoil its decisions. Among the result of the successive judicial developments passed by the French State Council was the inventing of new theories seeks through to realize an effective control upon the administration estimations in all their administrative activity fields. Among these theories is the budget theory between benefits and damages established via its decision issued in the case of (Ville Novelle Est) dated 28/05/1971. In the light of this theory, the French State Council started to make the budget theory between benefits and damages or the privileges and damages that may be imposed upon the decisions issued by the administration to dispossession for the public benefit and estimating the legitimacy of these decisions as a result of that. So we will tackle in our humble research the concept of balancing between the benefits and damages in the field of possession and the attitude of doctrine whether it is with or against applying and adapting them and the pretension of each one. Then we will illustrate the most important applications of the French administrative judging for the theory of balancing in the field of possession in . We will also talk about the attitude of the Egyptian and the Moroccan and the Libyan and the Jordian administration judging from this theory, After that we will conclude with the most important result and recommendation which we research in our humble research.
782810
Keywords: نزع الملكية -- المصلحة العامة -- القانون الفرنسي -- العالم العربي -- القوانين والتشريعات